Design and Implementation of a Waste Bank Application and Volunteer Platform for Marine Waste Reduction on the Southern Coast of Java - Danny, Ramanda; Saputra, Indra; Dealank, Reynant Phaza (Information Technology and Science (ITScience), 2025)
Marine waste along the southern coast of Java, Indonesia, presents a critical environmental issue caused by ocean currents, tourism, and local industrial activities. This accumulation disrupts marine ecosystems and threatens the livelihoods of coastal communities. The lack of accessible and efficient waste management systems exacerbates the problem, highlighting the need for innovative solutions to foster community involvement and environmental awareness.To address this challenge, this study introduces a waste bank application prototype designed specifically for the region using a design thinking approach. This methodology involved five stages: Empathize, Define, Ideate, Prototype, and Test. Data collection included interviews and surveys with local stakeholders, which identified key needs such as waste accumulation tracking, incentive-based participation, volunteer coordination, and environmental education for children. These findings guided the development of features like a contribution-based incentive system, event coordination, and a game to teach waste separation to younger users.The prototype underwent independent testing to evaluate its usability and effectiveness. Results demonstrated that the application successfully enhanced community engagement, offering a user-friendly platform that combines waste management with education. The inclusion of real-time tracking and rewards motivated active participation, while the educational game increased awareness among children.This study underscores the importance of collaborative, user-centered technology in addressing environmental challenges and provides a scalable model for sustainable waste management in coastal regions.